2010
DOI: 10.1186/1471-2202-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Neural expression and post-transcriptional dosage compensation of the steroid metabolic enzyme 17β-HSD type 4

Abstract: BackgroundSteroids affect many tissues, including the brain. In the zebra finch, the estrogenic steroid estradiol (E2) is especially effective at promoting growth of the neural circuit specialized for song. In this species, only the males sing and they have a much larger and more interconnected song circuit than females. Thus, it was surprising that the gene for 17β-hydroxysteroid dehydrogenase type 4 (HSD17B4), an enzyme that converts E2 to a less potent estrogen, had been mapped to the Z sex chromosome. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 75 publications
(106 reference statements)
0
24
0
Order By: Relevance
“…The formation of neurosteroids in the brain was originally demonstrated in mammals by the group of Baulieu 30 years ago (Compagnone et al, 1995;Corpéchot et al, 1981Corpéchot et al, , 1983Jo et al, 1989;Lanthier and Patwardhan, 1986;Mathur et al, 1993;Mellon and Deschepper, 1993;Robel and Baulieu, 1985;Robel et al, 1987). De novo synthesis and biological actions of neurosteroids in the brain of other vertebrates have also been established by my group and the groups of Vaudry, Schlinger, Kah, and others (in birds: Freking et al, 2000;London and Schlinger, 2007;London et al, 2003London et al, , 2006London et al, , 2010Matsunaga et al, 2001Matsunaga et al, , 2002Schlinger et al, 1999;Soma et al, 2004;Tam and Schlinger, 2007;Tsutsui and Schlinger, 2001;Tsutsui and Yamazaki, 1995;Tsutsui et al, 1997Tsutsui et al, , 1999Tsutsui et al, , 2003Ukena et al, 1999Ukena et al, , 2001Usui et al, 1995;Vanson et al, 1996;in amphibians: Beaujean et al, 1999;Bruzzone et al, 2010;Do-Rego et al, 2007;Inai et al, 2003;Matsunaga et al, 2004b;Mensah-Nyagan et al, 1994, 1996a, 1996bTakase et al, 1999Takase et al, , 2002…”
Section: Overviewmentioning
confidence: 88%
“…The formation of neurosteroids in the brain was originally demonstrated in mammals by the group of Baulieu 30 years ago (Compagnone et al, 1995;Corpéchot et al, 1981Corpéchot et al, , 1983Jo et al, 1989;Lanthier and Patwardhan, 1986;Mathur et al, 1993;Mellon and Deschepper, 1993;Robel and Baulieu, 1985;Robel et al, 1987). De novo synthesis and biological actions of neurosteroids in the brain of other vertebrates have also been established by my group and the groups of Vaudry, Schlinger, Kah, and others (in birds: Freking et al, 2000;London and Schlinger, 2007;London et al, 2003London et al, , 2006London et al, , 2010Matsunaga et al, 2001Matsunaga et al, , 2002Schlinger et al, 1999;Soma et al, 2004;Tam and Schlinger, 2007;Tsutsui and Schlinger, 2001;Tsutsui and Yamazaki, 1995;Tsutsui et al, 1997Tsutsui et al, , 1999Tsutsui et al, , 2003Ukena et al, 1999Ukena et al, , 2001Usui et al, 1995;Vanson et al, 1996;in amphibians: Beaujean et al, 1999;Bruzzone et al, 2010;Do-Rego et al, 2007;Inai et al, 2003;Matsunaga et al, 2004b;Mensah-Nyagan et al, 1994, 1996a, 1996bTakase et al, 1999Takase et al, , 2002…”
Section: Overviewmentioning
confidence: 88%
“…A recent flurry of investigations into dosage compensation have shown that several animals with differentiated sex chromosomes have varying degrees of compensation and often only a small proportion show complete dosage compensation between males and females (Itoh et al 2007;Deakin et al 2008a;Mank 2009;Itoh et al 2010;London et al 2010;Vicoso and Bachtrog 2011;Wolf and Bryk 2011).…”
Section: Does XCI In Marsupials Results In Dosage Compensation Betweenmentioning
confidence: 99%
“…The discovery that StAR, CYP11A1, 3β-HSD, CYP17, aromatase, and 17β-HSD are expressed in the zebra finch brain as early as posthatch days 1 and 5 demonstrated that the brain could synthesize estradiol de novo at the earliest stages of posthatch development [107; 108; 114; 115]. In situ hybridization mapping of these genes revealed how neurosteroids might exert their effects on the developmental organization of song nuclei: by producing steroids in the cell proliferative zone surrounding the lateral ventricle (Figure 3).…”
Section: Core Principle 2: Neurosteroidogenesis and Brain Organizatiomentioning
confidence: 99%
“…Proliferative activity in zebra finches is much lower in older birds than in young ones, and the ventricular zone is shallower. Consequently, it was much more difficult to conclude that StAR, CYP11A1, 3β-HSD, and CYP17 were specifically expressed within the proliferative zones of the lateral ventricle in adults [107; 108; 115]. In adult zebra finches and other songbirds, however, rates of proliferation and recruitment of new neurons into existing brain nuclei are not static and are correlated with changes in learned behavior, including song [133; 134]; this may in part explain the differences in adult cell proliferation rates between birds that do not learn song as adults (e.g.…”
Section: Core Principle 2: Neurosteroidogenesis and Brain Organizatiomentioning
confidence: 99%
See 1 more Smart Citation